THE EFFECT OF CONCENTRATION TRAINING AND IMAGERY TRAINING ON SELF-CONFIDENCE IN DOLLY CHAGI KICKS IN TAEKWONDO ATHLETES - shilvia, shilvia arienda; Hendra, Jhony; Saleh, Khairul; Saputra, Deka Ismi Mori; Susanti, Desi Tri (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
The dollyo chagi kick is one of the kicking techniques in taekwondo that is performed by lifting the leg and kicking forward, sideways, upward, downward, and backward to score points. The purpose of this study was to determine the effect of concentration training and imagery training on the self-confidence of Gema Cita Perkasa taekwondo athletes in performing the dollyo chagi kick. This study employs a quantitative descriptive research design using an experimental method with a two-group pre-test and post-test design. The sample selection in this study uses purposive sampling technique, with group division using ordinal pairing technique. The sample in this study consisted of 16 athletes. The instruments used in this study were questionnaires and interviews. The data analysis methods used were normality, homogeneity, reliability, and hypothesis testing with a significance level of α 0.05. Based on the results of the hypothesis test analysis, a significance value (sig. 2-tailed) of 0.650 was obtained, which is greater than 0.05, indicating that there is no effect of concentration training on self-confidence in dollyo chagi kicks among Gema Cita Perkasa taekwondo athletes. Furthermore, the hypothesis test yielded a significance value (sig. 2-tailed) of 0.652, which is greater than 0.05, indicating that there is no significant effect of imagery training on self-confidence in the dollyo chagi kick of Gema Cita Perkasa taekwondo athletes. Furthermore, the hypothesis test results yielded a significance value (sig.2-tailed) of 0.975, which is greater than 0.05, indicating that ‘there is no significant effect between concentration training and imagery training on self-confidence in the dollyo chagi kick of Gema Cita Perkasa taekwondo athletes.